Antecedent of Intention to Use Electric Vehicle Rental Applications - Sukboonpeng , Panwad; Simakhajornboon, Panuschagone (Journal of Modern Learning Development, 2024)
The objective of this research was to investigate the factors that influence the intention to use electric car rental applications. This quantitative study focused on customers of electric car rental companies residing in Bangkok. The sample size, determined using the G*Power 3.0.10 program based on test power, consisted of 260 participants. Questionnaires were disseminated via social media, and the data was subsequently analyzed using a structural equation model (SEM). The results revealed the following: Design perception (PD) had a positive influence on the perception of ease (PEU) (β = 0.310, C.R. = 2.224, p < 0.01) and perception of utility (PU) (β = 0.997, C.R. = 5.586, p < 0.01). Perceived safety (PS) influenced the perception of ease (β = 0.650, C.R. = 4.345, p < 0.01). However, it did not influence perceived benefits (β = 0.568, C.R. = 5.341, p < 0.01). No variable exhibited an influence on perceived benefits (β = 0.191, C.R. = 0.470, p = 0.638). Nonetheless, perceived benefits did influence the intention to use (IU) (β = 0.576, C.R. = 5.610, p < 0.01), as did some other factors, including one with an intention to use coefficient of β = 0.778, C.R. = 5.610, p < 0.01. The structural equation model (SEM) could predict 93.5% of the variability in the dependent variables (R2 = 0.935; R2Adj = 0.934). In conclusion, when developing applications for electric car rentals, developers should consider factors such as design recognition, safety awareness, perceived ease, and perceived usefulness.